Ten-core versus 16-core transrectal ultrasonography guided prostate biopsy for detection of prostatic carcinoma: a prospective comparative study in Indian population - V. Surya Prakash; G. Chandra Mohan; S. Venkata Krishnaiah; V. Vijaykumar; G. Ramesh Babu; G. Vijaya Bhaskar Reddy (Prostate International, 2013)
To compare the cancer detection rate in patients with raised serum prostate-specific antigen (PSA) or abnormal digital rectal examination (DRE) results between the 10-core and the 16-core biopsy techniques in an Indian population. Methods: Between November 2010 and November 2012, 95 men aged >50 years who presented to the Urology Department with lower urinary tract symptoms, elevated serum PSA, and/or abnormal DRE findings underwent transrectal ultrasonography (TRUS)-guided prostate biopsy. A total of 53 patients underwent 10-core biopsy and 42 patients underwent 16-core biopsy. Results: Of the 53 men in the 10-core group, 8 had cancer, whereas in the 16-core biopsy group, 23 of 42 men had cancer. Detection of prostate cancer was significantly higher in patients who underwent 16-core biopsy than in those who underwent 10-core biopsy (P<0.001). Among the 95 men, 44 men had abnormal DRE findings (46.3%), of whom 23 showed cancer (52.27%). Of 51 men with normal DRE findings and elevated PSA, 8 men had malignancy with a cancer detection rate of 15.68%. Among 20 men with PSA between 4.1 and 10 ng/mL, 2 (10%) had cancer. In 31 men with PSA between 10.1 and 20 ng/mL, 3 cancers (9.67%) were detected, and in 44 men with PSA >20 ng/mL, 26 cancers were detected (59.09%). Conclusions: The cancer detection rate with 16-core TRUS-guided biopsy is significantly higher than that with 10-core biopsy (54.76% vs. 15.09%, P<0.001). In patients with both normal and abnormal DRE findings, 16-core biopsy has a better detection rate than the 10-core biopsy protocol. With increasing PSA, there is a high rate of detection of prostate cancer in both 10-core and 16-core biopsy patients.